Gabapentin Is a Potent Activator of KCNQ3 and KCNQ5 Potassium Channels - Manville, Rían W. (Mol Pharmacol, 2018)
Synthetic gabapentinoids, exemplified by gapapentin and pregabalin, are in extensive clinical use for indications including epilepsy, neuropathic pain, anxiety, and alcohol withdrawal. Their mechanisms of action are incompletely understood, but are thought to involve inhibition of α(2)δ subunit–containing voltage-gated calcium channels. Here, we report that gabapentin is a potent activator of the heteromeric KCNQ2/3 voltage-gated potassium channel, the primary molecular correlate of the neuronal M-current, and also homomeric KCNQ3 and KCNQ5 channels. In contrast, the structurally related gabapentinoid, pregabalin, does not activate KCNQ2/3, and at higher concentrations (≥10 µM) is inhibitory. Gabapentin activation of KCNQ2/3 (EC(50) = 4.2 nM) or homomeric KCNQ3* (EC(50) = 5.3 nM) channels requires KCNQ3-W265, a conserved tryptophan in KCNQ3 transmembrane segment 5. Homomeric KCNQ2 or KCNQ4 channels are insensitive to gabapentin, whereas KCNQ5 is highly sensitive (EC(50) = 1.9 nM). Given the potent effects and the known anticonvulsant, antinociceptive, and anxiolytic effects of M-channel activation, our findings suggest the possibility of an unexpected role for M-channel activation in the mechanism of action of gabapentin.